GROSS DOMESTIC PRODUCT: PROBLEMS OF CONSTRUCTION AND USE IN ANALYSIS OF SOCIO-ECONOMIC PROCESSES - A. S. Abroskin; N. A. Abroskina; P. V. Petrov (Вестник университета)
The problematic aspects of the methodology for constructing gross domestic product indicator in macroeconomic statistics have been considered. Features of accounting for gross domestic product individual components in the System of National Accounts have been identified. Based on the analysis of international organizations recommendations, key aspects of improving the methodology for constructing this indicator taking into account the innovations in the System of National Accounts 2008 have been determined. Relevant issues of using gross domestic product in socio-economic analysis and supplements to the system of analytical indicators of the System of National Accounts with social indicators have been considered in the article.